2000
DOI: 10.1038/sj.ejhg.5200527
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of human longevity in Iceland

Abstract: The idea that human longevity is influenced by genetic factors has recently received strong support from work on other species. On the basis of partial population studies and selected kinships, significant correlations between the ages of parents and offspring have been reported, and some but not all twin studies have confirmed that human longevity is moderately inherited. However, studies based upon a relatively small proportion of a population are susceptible to sampling error and selection bias. Here we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
141
0
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(160 citation statements)
references
References 23 publications
12
141
0
7
Order By: Relevance
“…In humans, the clustering of late deaths in families with many extremely long-living individuals has provided support for a genetic component to longevity (Gudmundsson et al 2000;Schoenmaker et al 2006). In twin studies, it has been estimated that genetic differences account for about a quarter of the variance in adult human lifespan (Herskind et al 1996;Skytthe et al 2003).…”
Section: Geneticsmentioning
confidence: 99%
“…In humans, the clustering of late deaths in families with many extremely long-living individuals has provided support for a genetic component to longevity (Gudmundsson et al 2000;Schoenmaker et al 2006). In twin studies, it has been estimated that genetic differences account for about a quarter of the variance in adult human lifespan (Herskind et al 1996;Skytthe et al 2003).…”
Section: Geneticsmentioning
confidence: 99%
“…Our results showed that the estimated genetic component from the family and twin data can be equally matched by the contribution from a couple of very strong effect genes or by that from several thousand small effect genes [Vaupel and Tan, 1998;Begun et al, 2000]. If the genetic component to longevity is due to one or a few genes [Gudmundsson et al, 2000], according to our simulation, the nonparametric method could be a useful tool to help mapping them. On the other hand, if multiple genes with only small effects are involved [Cournil and Kirkwood, 2001;Carnes and Olshansky, 2001], one will have the power problem, especially when only limited samples are available.…”
Section: Discussionmentioning
confidence: 79%
“…We selected 8 SNPs on 8q24 that were significantly associated with PCa risk in 6 previous GWASs of European and American populations (p<10-8) (Gudmundsson et al, 2007;Yeager et al, 2007;Eeles et al, 2008;Eeles et al, 2009;Gudmundsson et al, 2009), and in a multiethnic cohort study of a functional locus (Jia et al, 2009). These loci are included in three independent regions on 8q24.…”
Section: Snp Selection For Evaluation and Genotypingmentioning
confidence: 99%
“…To date, GWAS have revealed 16 loci on chromosomal band 8q24 associated with PCa risk in various populations worldwide (Amundadottir et al, 2006;Gudmundsson et al, 2007;Haiman et al, 2007;Robbins et al, 2007;Schumacher et al, 2007;Yeager et al, 2007;Eeles et al, 2008;Salinas et al, 2008;Tan et al, 2008;Terada et al, 2008;Terada et al, 2008;Thomas et al, 2008;Al Olama et al, 2009;Chen et al, 2009;Eeles et al, 2009;Gudmundsson et al, 2009;Liu et al, 2009;Chen et al, 2010;Liu et al, 2010;Takata et al, 2010;Zheng et al, 2010;Adam et al, 2012), in 3 noted PCa risk regions on 8q24 [represented by single nucleotide polymorphisms (SNPs) rs1447295 (region 1), rs16901979 (region 2), and rs6983267 (region 3)]. We hypothesize the SNPs at 8q24 in Chinese population may behave differently from in other ethnicity and region.…”
Section: Introductionmentioning
confidence: 99%